Persepsi Konsumen terhadap Beras Organik dan Anorganik di Toko Satvika Boga Sanur Denpasar - DEWI, IDA AYU RATIH PRAVITA; SUDARTA, WAYAN; USTRIYANA, I NYOMAN GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.2, No.2, April 2013, 2013)
Normal 0 false false false EN-US X-NONE X-NONE ABSTRACT Consumers’ Perception toward Organic and Inorganic Rice at Satvika Boga Shop in Sanur Denpasar The objective of this research is to know the consumers’ perception level toward organic and inorganic rice and to know the consumers’ perception differences toward organic and inorganic rice. The research is descriptive by nature. Primary data was obtained from direct observation in the field and interview using questionnaire, meanwhile secondary data was obtained from the agencies/institutions. Previously the data that was obtained from the respondents was analyzed beforehand using validity and reliability tests. In this research using qualitative descriptive analysis method with Likert scale, descriptive statistic analysis, and nonparametric differentiation test analysis with Wilcoxon method. Respondents’ perception toward organic and inorganic rice equally included in good category with different score achievement, that is 81,86% for organic rice and 71,55% for inorganic rice. There is an obvious difference of respondents’ perception between organic and inorganic rice. It is can be seen from the statistic analysis result which shows Z value at -4,799 with the Asymp. Sig at 0,000 . The shop owner is expected to be always able to maintain the quality of organic rice, the government should provide the subsidy for organic rice and the farmers need the assistances from the related agencies (agricultural instructors) in the case of pesticide usage reduction and chemical fertilizer and consumers should be more careful to select the appropriate rice either from the hygienic and quality aspects. Key words: perception, organic and inorganic rice consumers.